A research proposal on understanding causes of high prevalence of pueperal sepsis at Koche health centre, Mangochi. - Mboma, Lusekero (Kamuzu University of Health Sciences, 2022)
Puerperal sepsis is one of the major causes of maternal death that accounts for 15 per cent of all maternal deaths in developing countries. This has prompted the researcher to explore causes of high prevalence of puerperal sepsis at Koche Health Centre in Mangochi District which reported high prevalence of the condition. The objectives of the study are; to assess knowledge of puerperal sepsis amongst women in the postpartum period; to assess the environment in which delivery is taking place; to identify any problems faced during ante, intra and post partum; and to assess cultural practices towards pregnant and post natal women. This will be a descriptive qualitative study that will utilise an in-depth interview guide to collect data. A sample of 10 mothers that have ever suffered from puerperal sepsis will be selected using purposive sampling